Clinical response of CARD14‐associated papulosquamous eruption to an anti‐interleukin‐17A antibody. (20th May 2022) - Klein, Benjamin; Treudler, Regina; Dumann, Konstantin; Boldt, Andreas; Schumann, Isabell; Simon, Jan C.; Kunz, Manfred
Abstract : Here we present another family with CARD14‐associated papulosquamous eruption, which is characterized by mutations in CARD14 and skin lesions resembling psoriasis and pityriasis rubra pilaris. We show beneficial therapeutic response to anti‐IL17A treatment in one patient and performed immunomonitoring of our patient, exhibiting enhanced pSTAT3 levels in T cells before treatment, which normalized after treatment. Together, our data support the pathogenic role of IL‐17A in this disease, which might have consequences for future treatment decisions in this rare condition.